2007
DOI: 10.1007/s11207-007-0330-7
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Measuring the Flux Reconnected and Ejected by the Two-Ribbon Flare/CME Event on 7 November 2004

Abstract: Observations of the large two-ribbon flare on 7 November 2004 made using SOHO and TRACE data are interpreted in terms of a three-dimensional magnetic field model. Photospheric flux evolution indicates that −1.4 × 10 43 Mx 2 of magnetic helicity was injected into the active region during the 40-hour buildup prior to the flare. The magnetic model places a lower bound of 8 × 10 31 ergs on the energy stored by this motion. It predicts that 5 × 10 21 Mx of flux would need to be reconnected during the flare to relea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
107
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 113 publications
(115 citation statements)
references
References 63 publications
5
107
3
Order By: Relevance
“…Various measurements indicate that the total magnetic flux of a single active region is about 10 22 Mx (Longcope et al 2007;Jeong and Chae 2007;Magara 2008). Thus, the measured total polar flux barely corresponds to that of single active region.…”
Section: Total Magnetic Fluxmentioning
confidence: 99%
“…Various measurements indicate that the total magnetic flux of a single active region is about 10 22 Mx (Longcope et al 2007;Jeong and Chae 2007;Magara 2008). Thus, the measured total polar flux barely corresponds to that of single active region.…”
Section: Total Magnetic Fluxmentioning
confidence: 99%
“…Quantitative studies of F and H both in MCs and in the solar corona are used to relate MCs to their solar sources (using F and H approximative conserved properties). Moreover, these studies set constrains to coronal magnetic configurations and on flux rope formation/eruption models Luoni et al 2005;Attrill et al 2006;Longcope et al 2007;Qiu et al 2007;Harra et al 2007;Mandrini et al 2007;Rodriguez et al 2008;Möstl et al 2008;Ravindra et al 2011). Lepping et al (2011) studied some properties of MCs observed at one astronomical unit by the spacecraft Wind in the two last solar minima.…”
Section: Magnetic Flux and Helicitymentioning
confidence: 99%
“…This possibility should be borne in mind as it influences the MC magnetic flux budget, which is important for establishing the Sun -Earth link (e.g. Longcope et al, 2007;Qiu et al, 2007;Démoulin, 2008;Möstl et al, 2009). However, aside from very few events (Mulligan et al, 1999;Mulligan and Russell, 2001), the shape of the MC cross-section and its longitudinal extent are not well known due to a lack of suitable multi-spacecraft observations.…”
Section: Introductionmentioning
confidence: 99%